Effects of low-dose filtered kretek cigarette smoke on bronchial smooth muscle in male Sprague-Dawley rats - Tjahyadi, David; Parwanto, Edy; Sisca, Sisca; Xavierees, Endrico; Jaya Edy, Hosea; Digambiro, Reza Aditya; Oladimeji, Ashaolu Victoria; Tjahyadi, Joey Joshua Vidova; Gabrielle, Laurentia (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundKretek cigarettes contain less nicotine and tar than conventional cigarettes. Exposure to cigarette smoke occurs mainly in the respiratory tract, resulting in histometric changes. The aim of this study was to evaluate the effect of filtered kretek cigarette smoke on bronchial histometric measurements in male Sprague-Dawley rats. MethodsAn experimental laboratory study was conducted involving 18 male Sprague-Dawley rats, aged 2-3 months, ranging from 150 to 250 grams in body weight. They were randomized into group 1 (controls) and experimental groups 2 and 3. Group 2 was exposed to filtered cigarette smoke at a dose of 1 stick/day and group 3 to 2 sticks/day. Treatment time for all groups was 30 days. Observation of bronchial histometric measurements of the lumen include, length, width, area, and perimeter. In addition, the bronchial mucosal and smooth muscle layers were also measured. The one way-ANOVA test was used to analyze the data. ResultsThe mean area and mean perimeter of the bronchial lumen of the rats were significantly greater in group 1 than in groups 2 and 3 (p=0.000). The mean bronchial smooth muscle area of the rats in group 1 was smaller than the mean in group 2, which was in turn smaller than the mean in group 3 (p=0.000). Apparently the rats in the treatment groups had undergone bronchoconstriction. ConclusionExposure to filtered kretek cigarette smoke at a dose of 1 stick/day as well as 2 sticks/day for 30 days caused bronchial mucosal hyperplasia and bronchoconstriction in male rats.